KONSEP TOTAL QUALITY MANAGEMENT DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM - Pettalongi, Sagaf S. (Hunafa: Jurnal Studia Islamika, 2010)
Curriculum is one of such vital important instruments in developing an educational institution that it should be designed in an effective manner in order to describe both direction and goal to be realized in Islamic education. A good curriculum is that which accommodates and meets communityâs needs and their environments, that is, having relevance and orientation to customersâ need in education and job opportunities. To achieve this goal, educational institutions have to incorporate total quality management principles whose main emphasis is totally on satisfying services to customersâ needs.Kata Kunci: Total Quality Management, kurikulum Â pendidikan Islam